Clinical governance; How been understood, what is needed? Nurses' perspective - Homayoun Sadeghi Bazargani; Mohammad Saadati; Jafar Sadegh Tabrizi; Gisoo Alizadeh; Roya Hassanzadeh; Ali Jannati (Patient Safety and Quality Improvement Journal, 2015)
Introduction: Clinical Governance (CG) is an overarching concept, using organizational capacity, safeguards high standards of the health services and provides a safe care for patients.  The aim of this research was to study nurses’ perception about Clinical Governance. Materials and Methods: A qualitative study was done with Focus Group Discussions (FGD). Purposeful Sampling was used to select the objectives including 65 participants. Actually 7 FGD’s were held. Content analysis was used to extract the meaningful themes. Results:Nurses believed that patient centeredness and evidence based practice is the core of the CG concept. Also they mentioned that cultural change, staffs training, adequate financial and human resources are required to successfully implementation of CG in hospitals.  Conclusion: Spreading up a shared vision about CG and providing the required infrastructures in hospitals would be facilitate CG initiatives. Proper commitment of the managers and staff participation could lead an effective CG implementation.